2016
DOI: 10.3109/13880209.2016.1141222
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic and cytoprotective effect ofEnicostemma littoraleagainst oxidative stress in Islets of Langerhans

Abstract: Context Oxidative stress induces apoptosis within Islets of Langerhans in diabetes mellitus (DM).Enicostemma littorale blume, herb of the Gentianaceae family is used as an anti-diabetic agent across rural India. Objective This report demonstrates potent anti-apoptotic and cyto-protective activity of Enicostemma littorale MeOH extract (EL MeOH ext.) against 50 mM H 2 O 2 in isolated rat Islets. Materials and methods In this study, the whole plant methanolic extract of EL with doses 0.25-4 mg/mL each for the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…In addition, we used ultra-thin sections and cell nucleus extraction methods to determine the concentration of chromatin. The results were similar to those of oxidative stress-induced apoptosis in the diabetic islet cells ( Srivastava et al, 2016 ) and suggested that the pulp cells of bitter pit undergo PCD. PCD is a physiological activity that regulates the body through active cell death ( Hautegem et al, 2015 ).…”
Section: Discussionsupporting
confidence: 82%
“…In addition, we used ultra-thin sections and cell nucleus extraction methods to determine the concentration of chromatin. The results were similar to those of oxidative stress-induced apoptosis in the diabetic islet cells ( Srivastava et al, 2016 ) and suggested that the pulp cells of bitter pit undergo PCD. PCD is a physiological activity that regulates the body through active cell death ( Hautegem et al, 2015 ).…”
Section: Discussionsupporting
confidence: 82%
“…The UV-vis absorption spectrum showed the maximum absorbance peak at 416 nm. In recent contributions, the synthesis of nanoparticles using bacteria including Pseudomonas deceptionensis, Weissella oryzae [70], Bacillus amyloliquefaciens, Bacillus licheniformis, and Rhodobacter sphaeroides [71][72][73] was reported. The extracellular synthesis of AgNPs was reported with the use of bacteria such as Acinetobacter calcoaceticus [74], Gluconobacter roseus [75], Klebsiella pneumonia [76], Salmonella typhimurium [77], Pseudomonas aeruginosa [78], Xanthomonas oryzae [79], and Rhodococcus sp.…”
Section: Synthesis Of Agnps Using Bacteriamentioning
confidence: 99%
“…Also the extract complies for heavy metal and microbial count as per the regulatory guideline 35,36 . The methanolic extract was reported to reduce the oxidative stress, induce apoptosis of cells and prolong survival of the tumor bearing mice 37,38 . The present study suggests that the alcoholic extract might be responsible for the anticancer activity in HCC in a similar way as reported in the literature.…”
Section: Discussionmentioning
confidence: 99%